Response of summer maize growth to drought-flood abrupt alternation - Bi, Wuxia; Weng, Baisha; Yan, Denghua; Zhang, Dawei; Liu, Cuishan; Shi, Xiaoliang; Jing, Lanshu; Yan, Siying; Wang, Hao (Frontiers in Earth Science, 2023)
Extreme events normally have negative effects on crop growth. Many studies have reported findings on drought and flood events, while only sparse studies have focused on new types of extreme events, such as drought-flood abrupt alternation (DFAA). We attempted to gain an insight on the effects of DFAA over two-year field experiment on biomass, grain yield and quality, then simulated the yield loss to DFAA in history and future in summer maize planting area in the Northern Anhui Plain. Results show that DFAA significantly reduced root biomass and shoot biomass by 77.1% and 60.1% compared with that in the control systems. The negative effect lasted until mature stage. The grain yield loss was 14.1%–38.4% in different DFAA treatments. The numerical simulation reveals that the average annual yield loss due to DFAA has been increasing in the Northern Anhui Plain, with 21.19%–30.98% during 1964–2017, 14.10%–33.40% during 2020–2050. The spatial distribution of yield loss changed as well. This study increases our knowledge of the effects of DFAA on crop production and highlights the need to consider the targeted countermeasures.